Processing and reporting monitoring and evaluation data - Mercado, Cesar Matamorosa 1938- (Quezon City Development Consultants for Asia Africa Pacific, 2004)
Purpose: A compilation of four articles of Cesar M. Mercado PH.D which illustrates the whole process in processing and reporting."
Article I : Physical and financial monitoring -- Article II : Reaction - leaning evaluation -- Article III : Skill evaluation -- Article IV : Performance evaluation.
Keywords: Participatory monitoring and evaluation (Project management); Project management -- Handbooks, manuals, etc